Autism-Like Behavior in BTBR Mice Is Improved by Electroconvulsive Therapy - Hagen, Eunice (Neurotherapeutics, 2015)
Autism is a developmental disorder characterized by impairments in social and communication abilities, as well as by restricted and repetitive behaviors. Incidence of autism is higher than earlier estimates, and treatments have limited efficacy and are costly. Limited clinical and experimental evidence suggest that patients with autism may benefit from electroconvulsive therapy (ECT). We examined the therapeutic potential of ECT in BTBR T+ tf/j mice, which represent a validated model of autism. A series of 13 electroconvulsive shocks (ECS) delivered twice a day over 7 days reversed core autism-like behavioral abnormalities—impaired sociability, social novelty, and repetitive behavior—when the animals were tested 24 h after the last ECS. The effect lasted up to 2 weeks after ECT. Neither single ECS nor a series of 6 ECS modified animals’ behavior. Chronic infusion into the lateral brain ventricle of a preferential oxytocin receptor blocker (2S)-2-Amino-N-[(1S,2S,4R)-7,7-dimethyl-1-[[[4-(2-methylphenyl)-1-piperazinyl]sulfonyl]methyl]bicyclo[2.2.1]hept-2-yl]-4-(methylsulfonyl)butanamide hydrochloride abolished ECT-induced improvement of sociability and mitigated improvement of social novelty but did not affect ECT-induced reversal of repetitive behavior. These proof-of-principle experiments suggest that ECT may, indeed, be useful in the treatment of autism, and that its therapeutic effects may be mediated, in part, by central oxytocin signaling. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13311-015-0357-7) contains supplementary material, which is available to authorized users.